Potential Strategies to Improve the Effectiveness of Drug Therapy by Changing Factors Related to Tumor Microenvironment - Cao, Dehong; Naiyila, Xiaokaiti; Li, Jinze; Huang, Yin; Chen, Zeyu; Chen, Bo; Li, Jin; Guo, Jianbing; Dong, Qiang; Ai, Jianzhong; Yang, Lu; Liu, Liangren; et al. (Frontiers in Cell and Developmental Biology, 2021)
A tumor microenvironment (TME) is composed of various cell types and extracellular components. It contains tumor cells and is nourished by a network of blood vessels. The TME not only plays a significant role in the occurrence, development, and metastasis of tumors but also has a far-reaching impact on the effect of therapeutics. Continuous interaction between tumor cells and the environment, which is mediated by their environment, may lead to drug resistance. In this review, we focus on the key cellular components of the TME and the potential strategies to improve the effectiveness of drug therapy by changing their related factors.